EFEKTIVITAS PENGGUNAAN ILMU BANTU GRAFONOMI DAN SINAR ULTRAVIOLET DALAM PEMBUKTIAN TINDAK PIDANA PEMALSUAN UANG KERTAS RUPIAH - Pratama, Lucky Febrian Putra; Firganefi, Firganefi; Farid, Muhammad (Cahaya Ilmu Bangsa, 2025)
Money has been an integral part of human life since ancient times. In fulfilling human needs, money serves as the primary medium in economic transactions. The very important role of money encourages some individuals to seek illegal ways to obtain money, one of which is by counterfeiting Indonesian banknotes. This research aims to determine the effectiveness of using graphonomy and ultraviolet light in proving the crime of counterfeiting Indonesian banknotes. The normative juridical method is used to address the issues being researched, and the data collection process is carried out through literature study. The combination of these two auxiliary sciences not only meets the requirements as valid evidence in the Indonesian criminal justice system but also provides strong scientific evidence to support the prosecutor's position in court. Thus, the integration of graphonomy and UV light significantly contributes to enhancing the accuracy of forgery detection, strengthening public trust in the authenticity of money, and supporting national efforts in combating currency counterfeiting.